Once Upon a Word: Growing Young Minds with Picture Story Vocabulary Builders - Lemmuela Alvita Kurniawati; Felicia Vinanda Prasetya (ABDI: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
The current community service project aimed to meet the needs of a private elementary school in Yogyakarta by providing picture storybooks for 5th-grade students to enhance their English vocabulary mastery through reading activities. Five storybooks were created using a modified 4D development model (Define, Design, and Develop), aligning with biblical lessons and the school’s values. The design and development of the storybooks were based on a needs assessment conducted through interviews with English teachers and four students, as well as a questionnaire for the students. The storybooks were used as complementary materials in English classes to foster student vocabulary acquisition and introduce moral values and virtues in life. Each storybook includes a narrative, illustrations to stimulate creativity and imagination, a moral value section, and a vocabulary list. The community service project highlights the potential of storybooks to foster language acquisition and moral development. Future community service opportunities are also available.